Defining and unpacking the core concepts of pharmacology education - Marina Santiago; Elizabeth A. Davis; Tina Hinton; Thomas A. Angelo; Alison Shield; Anna‐Marie Babey; Barbara Kemp‐Harper; Gregg Maynard; Hesham S. Al‐Sallami; Ian F. Musgrave; Lynette B. Fernandes; Suong N. T. Ngo; et al. (Wiley, 2021)
Abstract Pharmacology education currently lacks a research‐based consensus on which core concepts all graduates should know and understand, as well as a valid and reliable means to assess core conceptual learning. The Core Concepts in Pharmacology Expert Group (CC‐PEG) from Australia and New Zealand recently identified a set of core concepts of pharmacology education as a first step toward developing a concept inventory-a valid and reliable tool to assess learner attainment of concepts. In the current study, CC‐PEG used established methodologies to define each concept and then unpack its key components. Expert working groups of three to seven educators were formed to unpack concepts within specific conceptual groupings: what the body does to the drug (pharmacokinetics); what the drug does to the body (pharmacodynamics); and system integration and modification of drug-response. First, a one‐sentence definition was developed for each core concept. Next, sub‐concepts were established for each core concept. These twenty core concepts, along with their respective definitions and sub‐concepts, can provide pharmacology educators with a resource to guide the development of new curricula and the evaluation of existing curricula. The unpacking and articulation of these core concepts will also inform the development of a pharmacology concept inventory. We anticipate that these resources will advance further collaboration across the international pharmacology education community to improve curricula, teaching, assessment, and learning.